Design: An interactive e-module based on ethnomathematics to improve numeracy skills of slow learners - Wahyu Widodo; Erni Puji Astuti (Indonesian Journal of Educational Development (IJED), 2026)
The numeracy skills of slow learners are very low, especially in understanding information, analyzing strategies, contextualizing solutions, and interpreting them. This study aims to analyze needs and design an interactive e-module based on ethnomathematics to improve numeracy skills of slow learners. This study employs the ADDIE model, focusing on the analysis and design stages. The subjects of this study involved mathematics teachers and slow learners. Slow learners were selected using purposive sampling techniques. Data were obtained through observations, interviews, questionnaires, and tests using instruments such as observation sheets, interview guidelines, questionnaires, and numeracy tests. Data analysis employed descriptive, qualitative, and quantitative approaches. The study's results indicate a gap between the availability of technological facilities and their use in mathematics learning. Technology integration remains limited, and ethnomathematics is rarely used as a learning context. The design stage produced an interactive e-module that integrates learning objectives, numeracy content, display design, interaction flow, and evaluation instruments tailored to the characteristics of slow learners. Therefore, it is necessary to develop an interactive e-module based on ethnomathematics to create an inclusive, engaging, and meaningful learning experience that supports the numeracy skills of slow-learning students.